حديث «من بدل دينه فاقتلوه» إشكاليته وحلوله بين المتقدمين والمتأخرين = Problem and Solution on the Ḥadīth "Whoever changes his religion, kill him": A Study of the Approaches of Traditional and Contemporary Scholars - Mohammed Yaqub, Mohammed Abullais Shamsuddin; Ahmad, Nadzrah; Fatah Yasin, Raudlotul Firdaus; Mohd. Marzuki, Zunaidah (IIUM, 2017)
This study seeks to reach the most appropriate understanding of the ḥadīth "whoever changes his religion, kill him". Having surveyed the views of traditional and contemporary scholars vis-a-vis their interpretation of this ÍadÊth and other similar Prophetic traditions, it is evident that there are various concerns and interpretations, ranging from killing the apostate instantly, killing after asking for repentance within a limited period, to killing after asking for repentance at any time. Afterwards, some scholars argued this ÍadÊth was indirect reference for giving deterrent punishment while others viewed that one cannot be incriminated at all on the course of changing his religion. Thus, it can be presumed that the interpretation of this ḥadīth has witnessed a kind of evolution to the direction of abstention from the killing of an apostate. This study notes the existence of some sort of correlation between these stages of evolution and the political, cultural and social situation prevailing in the Islamic state and among Muslims at the time of that respective phase. On the other hand, this study points out that there was no problem in the hadith during the era of the Companions and the followers of the Ṣaḥābah and their followers. Rather, no conflict was reported between this ḥadīth and the Qur’an except with some modern scholars when the idea of freedom and freedom of faith gained momentum. What is evident after a thorough analysis of maximum proofs of all variant opinions and their assessment is the assertion of wujËb upon the execution of the apostate after his atonement; although the nature of interval allowed for the atonement remains open to be decided by ruler of the state. The ruler is further authorized to contemplate on the socio-political and cultural scenario of the Islamic country and free to assess them, in a way which is conducive to ensure the realization of social benefit and to appreciate the pressing need of the retribution. It is, however, incumbent upon the ruler to compare the situation of capital punishment with another scenario of delaying it, which may be helpful to achieve any benefit. Likewise, he is also enjoined to block all the possible means failure of which may lead to the emergence of other apostates in the future, so as to facilitate them to draw lessons from the previous executions. Besides this, the researchers would like to suggest that there is a necessity of segregation between each and every apostate, so that it could reduce the intensity of peril caused by them towards others and the potential influence they will inflict upon the Islamic state, in general, and the other susceptible personalities, in particular.